IMPLEMENTATION OF PAGERANK ALGORITHM IN MATLAB - Aprilia, Rima; Sari, Rina Filia (UIN Sumatera Utara Medan, 2017)
Implementation of the PageRank algorithm to rank web generally only contain static and dynamic pages, with the rapid url users then needed an algorithm for calculating web rankings. In determining the ranking of a web, links incoming and outgoing links are also random surfer model is one decisive factor in determining the ranking of a web. Implementation of PageRank on MATLAB formed on a program in the m-file.